(untitled) (Scientific journal of the Fergana State University, 2026)
This article discusses the “AgroAI Drone” monitoring platform developed on the basis of artificial intelligence. The system enables farmers to increase crop productivity, reduce water and fertilizer consumption, detect soil salinity, and diagnose plant diseases at early stages. The integration of drones, IoT sensors, and artificial intelligence provides farmers with accurate real-time data and recommendations.